Occupational noise in urban busesa short review - Cvetkovi, M (2017)
The problem of noise in the public transportation bus and its effect to the driver must be considered systematically and examined in detail. The main aim of this short review is to approach the problem as detailed as possible, compare results and determine the effect(s) of the noise to the driver. For the purpose of this work the PRISMA Statement Methodology was applied. Were found 1119 articles and 14 included in this short review. Most of the results have been obtained using ANOVA Analysis and measurements that comply with standards (ISO 9612:2009, ISO 5128:1980, ISO 1999:1990). This paper illustrates the noise level variations depending on the city bus model, its age, engine position, and other factors that disturb the comfort of working space. Regarding the analysed results from the different papers, the noise depends mostly on the engine position in the bus. (c) 2017 Taylor & Francis Group, London.